Obtaining chicken primordial germ cells used for gene transfer: in vitro and in vivo results - Chojnacka-Puchta, Luiza (J Appl Genet, 2015)
Recently, several attempts have been made to create a generation of transgenic chickens via chimeric intermediates produced by primordial germ cells (PGCs) transfer. This study aimed to compare the influences of different chicken PGCs isolated from circulating blood (bPGCs) or gonads (gPGCs), purification (ACK, Percoll or trypsin) and transfection methods (electroporation or lipofection) on the expression of transgenes in vitro and the migration of modified donor cells to the recipient gonads. The highest average frequency of pEGFP-N1 plasmid-transfected bPGCs (75.8 %) was achieved with Percoll density gradient centrifugation and electroporation. After ammonium chloride-potassium (ACK) treatment and lipofection, in vitro transgene expression was only detected in 35.2 % of bPGCs. Chimeric chickens were produced from these purified, transfected and cultured cells, and the transgene was detected in the gonads of 44 and 42 % of the recipient embryos that had been injected with bPGCs and gPGCs, respectively. These data confirmed that the combination of PGC purification via Percoll centrifugation and electroporation was an effective method for producing transgenic chickens. Subsequently, we used this method with expression vectors for gene hIFNα 2a/hepatitis B virus surface antigen (HBsAg) under the control of the ovalbumin promoter to generate G0 transgenic chickens. Consequently, we observed that 4.9 % of the hens and 3.5 % of the roosters carried the hIFNα 2a gene, whereas 16.7 % of the hens and 2.4 % of the roosters carried the HBsAg gene, thus undisputedly confirming the exceptional effectiveness of the applied methods.